Toward a philosophy of public management education for the 1990s - Cardenas, Benito C. (Philippine Journal of Public Administration, 1990)
Philosophy provides the basic ingredient of values that we need as a beacon for the progress of the science and art of administration. Some propositions which may constitute parts of a philosophy to guide the teaching of public administration in the Philippines embrace (a) the development of a philosophy integrating ethics, art and science; (b) a balanced mix of fusing or separating politics and administration; and, (c) a realistic combination of the trivial routinary and noble pursuits in public management. This multidimensional task of rooting in and anchoring on a philosophy lends stability and sustainability to Public Management education if it is to pass the test of time.